Pemilihan Pemasok Baterai Forklift Elektrik dengan Menggunakan Metode AHP dan TOPSIS di Industri Manufaktur Otomotif - Satriyo Maulana; Anwar Martua Pasaribu; Winnie Septiani (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
The activity of the automotive manufacturing industry continues to increase. The selection of electric forklift battery suppliers needs to be done because they are environmentally friendly and do not produce air pollution. Supplier selection is very important in determining the speed of delivery and the quality of raw materials to be able to meet consumer demands quickly and with quality. The purpose of this research is to select the best battery supplier and in accordance with the company's qualifications. The method used in completing this research is the Analytical Hierarchy Process (AHP) and Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) in assisting decision-making. The AHP method is used to determine the most dominant criterion with a pairwise comparison matrix to determine the weight. Then the weight value is used as input in the calculation of the TOPSIS method to determine the ranking. The contribution of this research can be applied in the automotive manufacturing industry in selecting electric forklift battery suppliers. Based on the calculation results, it is known that the price criterion is the most dominant criterion with a weight of 0.463. Price is a parameter that is often used by every company. In addition to price criteria, there are also important criteria, including service life 0.270, quality 0.144, service 0.079, and flexibility 0.044. Based on TOPSIS calculations, it is known that the Rocket supplier is ranked 1st and is a priority to become a supplier in the selection of forklift batteries in the automotive manufacturing industry.